2019
DOI: 10.1111/aab.12491
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Pepino mosaic virus in tomato crops of Spain and Morocco

Abstract: Pepino mosaic virus (PepMV, genus Potexvirus) is an emergent and highly infectious pathogen responsible for economically important diseases in tomato crops. An extensive survey of tomato plants showing PepMV-like symptoms was carried out in 2017 to study the PepMV genetic diversity and populations structure in different tomato-producing areas of Spain and Morocco. Molecular dot-blot hybridization analysis showed that virus populations from Spain andMorocco were mainly composed of isolates belonging to the Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…We have addressed this aspect before by using different approaches, including comparing the PepMV-CH2 natural diversity in areas with only single infections vs areas with mixed infections ( Alcaide et al, 2020a ), and in a long-term in planta PepMV evolution experiment including temperature in its design as an environmental variable ( Alcaide et al, 2021 ). Regarding the first approach, we observed more variability for PepMV-CH2 in Mazarrón (mixed infections) than in Águilas (single infections), but further experiments failed to identify selective forces explaining this observation; moreover, in a different set of analyses, we identified important migration fluxes among geographical areas ( Gómez-Aix et al, 2019a ), and the effect of migration may blur conclusions ( Lapidot et al, 2014 ). Regarding the second study mentioned above, we observed complex interactions among variables including viral strain (CH2 vs EU), type of infection (single vs mixed), and temperature ( Alcaide et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We have addressed this aspect before by using different approaches, including comparing the PepMV-CH2 natural diversity in areas with only single infections vs areas with mixed infections ( Alcaide et al, 2020a ), and in a long-term in planta PepMV evolution experiment including temperature in its design as an environmental variable ( Alcaide et al, 2021 ). Regarding the first approach, we observed more variability for PepMV-CH2 in Mazarrón (mixed infections) than in Águilas (single infections), but further experiments failed to identify selective forces explaining this observation; moreover, in a different set of analyses, we identified important migration fluxes among geographical areas ( Gómez-Aix et al, 2019a ), and the effect of migration may blur conclusions ( Lapidot et al, 2014 ). Regarding the second study mentioned above, we observed complex interactions among variables including viral strain (CH2 vs EU), type of infection (single vs mixed), and temperature ( Alcaide et al, 2021 ).…”
Section: Discussionmentioning
confidence: 85%
“…In Spain, PepMV populations infecting tomato crops were composed of isolates belonging to the EU strain until 2005, when viral populations underwent a shift to become mainly formed by isolates belonging to the CH2 strain; isolates of the EU strain were maintained in minor proportions in mixed infections ( Pagán et al, 2006 ; Gómez et al, 2009 ). This epidemiological scenario seems to be long-lasting ( Gómez-Aix et al, 2019a ; Alcaide et al, 2020a ), in spite of the superior in planta fitness of CH2 isolates as compared to EU isolates ( Gómez et al, 2009 ; Alcaide et al, 2020a ). Broadening our understanding of this phenomenon is highly important, as the maintenance of mixed infections may have critical consequences on the PepMV evolutionary outcome.…”
Section: Introductionmentioning
confidence: 99%
“…PepMV‐MA17‐1, a virulent CH2 isolate was sampled from tomato plants showing severe symptoms in greenhouses in the locality of Chtouka (Region of Casablanca‐El Jadida, Morocco) in 2017 (Gómez‐Aix et al, 2019) and conserved at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Among them pepino mosaic virus (PepMV; genus Potexvirus , family Alphaflexiviridae ) represents one of the most threatening pathogens of tomato ( Solanum lycopersicum ) crops (Hanssen et al, 2010). Identified on pepino ( Solanum muricatum ) in 1974 from which the first isolated strain was identified as a Peruvian (LP) (Jones et al, 1980), it is considered today as a widespread viral disease affecting tomato crops, mainly in North America, Europe and North Africa, where four other strains were identified; the European (EU), the Chilean (CH2), the American (US1) and the new Peruvian (PES) (Gómez et al, 2009; Gómez‐Aix et al, 2019; Hanssen & Thomma, 2010; Hasiów‐Jaroszewska et al, 2009; Maroon‐Lango et al, 2005). Its genome consists of a positive sense, single‐stranded RNA of approximately 6400 nucleotides, harbouring five open reading frames (ORFs), which include an RNA‐dependent RNA polymerase (RdRp), a triple gene block (TGB) and a coat protein (CP) (Aguilar et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In tomato, fruit marbling symptoms are considered as the most important cause of significant economic losses around the world (Hanssen and Thomma, 2010;Hanssen et al, 2010b). PepMV is present in major tomato-growing areas of the Mediterranean (Gómez et al, 2012) and was recently reported in United States and Mexico (Ling and Zhang, 2011), South Africa (Carmichael et al, 2011), Spain and Morocco (Gómez-Aix et al, 2019), and Serbia (Stanković et al, 2020).…”
Section: Potexvirus: Pepino Mosaic Virus (Pepmv)mentioning
confidence: 99%